Partitioning Net Ecosystem Exchange (NEE) of CO2 Using Solar‐Induced Chlorophyll Fluorescence (SIF). Issue 4 (17th February 2021) - Kira, O.; Y‐Y. Chang, C.; Gu, L.; Wen, J.; Hong, Z.; Sun, Y.
Abstract: Accurate partitioning of net ecosystem exchange (NEE) of CO2 to gross primary production (GPP) and ecosystem respiration ( R eco ) is crucial for understanding carbon cycle dynamics under changing climate. However, it remains as a long‐standing problem in global ecology due to lack of independent constraining information for the two offsetting component fluxes. solar‐induced chlorophyll fluorescence (SIF), a mechanistic proxy for photosynthesis, holds great promise to improve NEE partitioning by constraining GPP. We developed a parsimonious SIF‐based approach for NEE partitioning and examined its performance using synthetic simulations and field measurements. This approach outperforms conventional approaches in reproducing simulated GPP and R eco, especially under high vapor pressure deficit. For field measurements, it results in lower daytime GPP and R eco than conventional approaches. This study made the first attempt to demonstrate SIF's potential for improving NEE partitioning accuracy and sets the stage for future efforts to examine its robustness and scalability under real‐world environmental conditions. Plain Language Summary: Knowing the exchanges of CO2 fluxes between terrestrial ecosystems (both natural and agricultural systems) and atmosphere is crucial for understanding and predicting the strength of land carbon sink under climate change. To date, we are only able to directly measure the net terrestrial CO2 fluxes at the ecosystem level and beyond, but not its constituent fluxes from photosynthesis and respiration. In this study, we developed an approach to partition the net CO2 flux to its two components with opposite signs: CO2 flux absorbed by plants (via photosynthesis, denoted as GPP), and CO2 flux emitted to the atmosphere by the plant and the soil (via autotrophic and heterotrophic respiration, denoted as ecosystem respiration), using remote sensing of Solar‐Induced chlorophyll fluorescence (SIF), a mechanistic proxy for photosynthesis. Our results show that using SIF to anchor GPP has the potential to enhance the accuracy of partitioned component fluxes, setting the stage for future efforts to further examine its global scalability toward closing the long‐standing knowledge gap in carbon flux partitioning. Key Points: We develop a parsimonious solar‐induced chlorophyll fluorescence (SIF)‐based net ecosystem exchange (NEE) partitioning method and examine its performance using synthetic simulations and field measurements The SIF‐based NEE partitioning more accurately reproduces the simulated true gross primary production (GPP) and ecosystem respiration ( R eco ) component fluxes than conventional approaches The SIF‐based approach results in lower daytime GPP and R eco than conventional approaches for field measurements